Valores gasométricos en población adulta y adulta mayor residente de gran altitud - Calderón Gerstein, Walter (2020)
Introduction. Arterial blood gas and electrolyte values undergo changes in high altitude, which can alter the diagnostic and prognostic evaluation of certain diseases. Objective. To determine the values of arterial gases and electrolytes in healthy adults and older adults in high altitude resident. Methods. Prospective, descriptive study, carried out with a population of healthy adults and elderly volunteers, at Ramiro Prialé Prialé National Hospital in EsSalud - Huancayo, a city located 3250 meters above sea level, whose barometric pressure is 515 mmHg. Arterial blood samples were taken from subjects and processed with Roche Omni C arterial gas analyzer. Continuous variables were analyzed with ANOVA and statistical analysis performed with Excel and SPSS. Results. 105 people from 30 to 87 years old were evaluated. The average of the analyzed variables was: hemoglobin 15,46 ± 2, blood oxygen pressure 59,27 ± 6,9, hemoglobin saturation 91,7 ± 3,2, pH 7,46 ± 0,28, blood pressure of CO2 28,68 ± 4,15, bicarbonate 20,54 ± 2,86, sodium 143,43 ± 5,6, potassium 3,56 ± 0,5 mEq / L. For each year of life, PaO2 decreased by 0,556 mmHg, oxygen saturation by 0,484%, and pO2 / FiO2 by 0,556. Conclusions. There is variation of both arterial gases and electrolytes at high altitude, which is accentuated with age and should be considered for the management of patients above 3000 masl.